Wolves in the Wolds: Late Capitalism, the English Eerie, and the Weird Case of 'Old Stinker' the Hull Werewolf. Issue 1 (May 2019) - George, Sam
Abstract : British folklore reveals a history of werewolf sightings in places where there were once wolves. I draw on theories of the weird and the eerie and on the turbulence of England in the era of late capitalism in my analysis of the representation of werewolves in contemporary urban myths. Werewolves are deliberately excluded from Mark Fisher's notion of the 'weird', because they behave in a manner that is entirely expected of them. I contradict this by interrogating the werewolf as spectre wolf, bringing it within the realms of the weird. In examining the Hull Werewolf, I put forward the suggestion that he represents not only our belief in him as a wolf phantom, but our collective guilt at the extinction of an entire indigenous species of wolf. Viewed in this way, he can reawaken the memory of what humans did to wolves, and redeem the Big Bad Wolf of our childhood nightmares.